Genetic polymorphism of blood potassium in goat belonging to the different breeds and subbreed in Mongolia - Myagmarsuren, P; Battsetseg, B; Altangerel, D; Dungu, D; Myagmardulam, U (Mongolian Journal of Agricultural Sciences, 2014)
In the goats belonging to the different breeds and sub breed the genetic polymorphism at the determinant locus of blood potassium was revealed by flame spectrophotometer method. The kalemic systems, in those breeds were characterized by a polymorphism of middle level due to the existence of the two phenotypes and of three genotypes. The polymorphic character of this system is given by the distributional discontinuity of potassium ions in whole blood, the discontinuous space ranging were 10-34 m eq/L in the Mongolian native breed, 0.38-20.3 m eq/L in the Govigurbansaihan breed, 10.27- 15.8 m eq/ L in the AltainUlaan sub breed. The remarkable differences in the whole blood of potassium concentrations were recognized between Mongol and Govi-Gurban Saikhan breeds td=6.46 or (p<0.001), Govi-Gurban Saikhan and Altai ulaan (td=5.7) or (p<0.001). As this trait, the slight difference was revealed between Mongol and Altai ulaan breeds (td=1.87) or (p>0.05). The correlation of the trait was also high r=0.57 between these breeds. The animals with potassium ion concentration below the discontinuity space are of LK type and those with ionic concentration above the discontinuity space are of HK type. The blood potassium level is determined by two alleles; KL and Kh, being in incomplete dominance relationship; the allele K L, responsible for low potassium, is dominant compared to its recessive Kh allele which causes high levels of blood potassium. These two alleles at the Ks locus, located on an autosomal chromosome, determine three genotypes; KLKL (dominant homozygote), KLKh (heterozygote), and KhKh (recessive homozygote). In the Mongolian native breed the allele Kh was less frequent (20%) than its dominant KL (80%), in the Govi Gurban Saihan breed, the frequency of the alleles were also 5 %, 95% respectively. The phenotype LK (80%-100%) achieved a much higher frequency than the phenotype HK (5%-20%) in those breeds. Consequently, the recessive homozygosis and heterozygosis recorded in an equally frequency (50%, 50%) in the Mongolian native breed, instead, the frequency of recessive homozygosis were slightly higher than heterozygosis (66%>34%) in the Govi Gurban Saihan. DOI: http://dx.doi.org/10.5564/mjas.v11i2.217 Mongolian Journal of Agricultural Sciences Vol.11(2) 2013 pp.54-58